2015
DOI: 10.1097/prs.0000000000001572
|View full text |Cite
|
Sign up to set email alerts
|

The Current Means for Detection of Migraine Headache Trigger Sites

Abstract: The authors' 15-year experience with migraine surgery has led them to believe that the most common reasons for incomplete response are failure to detect all of the trigger sites or, on rare occasions, inadequate surgery on the trigger sites. Thus, accurate identification of trigger sites is essential. The purpose of this article is to share the authors' current stepwise algorithm for accurately detecting the migraine trigger sites, which has evolved through surgery on nearly 1000 patients. To begin, a thorough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 27 publications
1
72
0
2
Order By: Relevance
“…This evidence was followed by a prospective study where he reported a 95% rate of either complete alleviation or improvement in MH after a mean follow-up of 1 year [5]. Over the last 15 years, Guyuron conducted several anatomical and clinical studies reporting a reduction of the frequency, duration, and intensity of MH by at least half in 80-90% of patients [4][5][6][7][8][9][10]. In 2011, Guyuron et al published a study examining the longterm benefits of migraine surgery where it was reported an 88% success rate after a 5-year follow-up (29% completely healed; 59% gained improvement; 12% did not show any change) [8].…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…This evidence was followed by a prospective study where he reported a 95% rate of either complete alleviation or improvement in MH after a mean follow-up of 1 year [5]. Over the last 15 years, Guyuron conducted several anatomical and clinical studies reporting a reduction of the frequency, duration, and intensity of MH by at least half in 80-90% of patients [4][5][6][7][8][9][10]. In 2011, Guyuron et al published a study examining the longterm benefits of migraine surgery where it was reported an 88% success rate after a 5-year follow-up (29% completely healed; 59% gained improvement; 12% did not show any change) [8].…”
Section: Resultsmentioning
confidence: 97%
“…MH characteristics (e.g., frequency, duration, and amount of drugs needed) also seem to affect the surgical outcome; milder MH have higher chances of improvement in comparison to more severe ones, which are more likely to recur postoperatively [5,8,9]. Preliminary Botox infiltration does not affect the surgical success [10].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations